Dealing with A State of Emergency: A Comparative Study Between Indonesia and Malaysia in Government Use for Pharmaceutical Products - Sulistianingsih, Dewi; Prasetyo Adhi, Yuli; Puji Lestari, Diaj; Binti Mohd Yusoff, Rahmawati (International Law Discourse in Southeast Asia, 2025)
The implementation of patents by the government has become a national policy to control the spread of COVID-19 by helping drug supplies in emergencies and urgent situations. The purpose of this research is to analyse patent regulation by the government (Government Use) for pharmaceutical products in the state of emergency in Indonesia by comparing with Government Use in Malaysia. This research is legal research using secondary data with qualitative analysis. The implementation of patents by the government on the Covid-19 drugs remdesivir and favipiravir, whose application in Indonesia has been based on the provisions regulated by TRIPS and the DOHA Declaration. The implementation of this policy is due to a very urgent need in efforts to tackle the COVID-19 pandemic. Malaysia has also implemented the same policy to address the need to import a generic version of the Hepatitis C drug. It is hoped that the implementation of patents by the Government on the drugs remdesivir and favipiravir can facilitate access for Covid-19 patients who need them and can be an effective strategy to deal with the Covid-19 outbreak.